Pengaruh Insentif dan Reward terhadap kinerja karyawan PT. Wan Setia - Chandra Priya Gunawan Abas; Andi Yusniar Mendo; Syamsul B. Biki (Economic Reviews Journal, 2025)
This study aims to examine the effect of incentives and rewards on employee performance, both partially and simultaneously. The study employed a quantitative method with a descriptive quantitative approach. Primary data were collected trough questionnaires distributed to PT employees Wan Setia. The sample consisted of 34 respondents, and the data were analyzed using multiple linear regression analysis. The result showed that: 1) incentive have a positive and significant effect on employee performance, (2) rewards have a positive and significant effect on employee performance, and (3) simultaneously, incentive and rewards have a significant effect on employee performance. The coefficient of determination in this study is 49.6%, indicating that 49.6% of the variability in employee performance can be explained by incentive and rewards.